A fluorescence toolbox: A review of investigation of electrophoretic separations, process, and interfaces. Issue 5 (25th September 2018) - Thompson, S.; Pappas, Dimitri
Abstract: This review focuses on fluorescence spectroscopy techniques for the investigation of electrophoretic separations. Fluorescence has been used as a sensitive detector for capillary, gel, and microchip electrophoresis for decades. However, advanced fluorescence methods can be used to study transport, interfacial phenomena, intermolecular and affinity interactions, and other processes that occur during separation. This so‐called spectroscopic toolkit can be implemented to understand fundamental behavior in electrophoresis and electrokinetic chromatography. Techniques such as fluorescence recovery after photobleaching, fluorescence correlation spectroscopy, and fluorescence anisotropy are discussed in relation to electrophoretic separations. Newer methods such as super‐resolution microscope are also introduced.